Autonomus vehicles: road issues - vital dilemmas technology takes the wheel - Cárdenas Krenz, Ronald (2019)
The article is a reflection since the law on the appearance of "autonomous vehicles", which have been emerging under the promise of a safer and cleaner alternative to the problems of insecurity and vehicular chaos, which affect us, derived from the lack of a culture of compliance with traffic rules, among other factors. However, this new technology is not exempt from risks and ethical and legal implications that must be noted before it reaches our environment, outlining the need for a regulatory and control framework that monitors the application and technology of these vehicles in order to offer the necessary guarantees to preserve in the best way not only the rights of the users of these cars but also of the pedestrians.